2017
DOI: 10.1080/21655979.2017.1373918
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of saccharification potential of recombinant xylanase from Bacillus licheniformis

Abstract: Saccharification potential of xylanase enzyme cloned from Bacillus licheniformis into E. coli BL21 (DE3) was evaluated against plant biomass for the production of bioethanol. The expression of cloned gene was studied and conditions were optimized for its large scale production. The parameters effecting enzyme production were examined in a fermenter. Recombinant xylanase has the ability to breakdown birchwood xylan to release xylose as well as the potential to treat plant biomass, such as wheat straw, rice stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…The reason of the difference may be due to the different enzyme resources, xylanase purity or the modified xylanase gene (PUCHART et al, 2018). It was reported that xylanase gene from Bacillus licheniformis was expressed in E.coli, the enzyme was effective for sugarcane bagasse saccharification (AFTAB et al, 2018), in agreement with this study. In addition, the xylanase from Aspergillus niger could improve the yields of glucose and arabinose effectively (p<0.05), which may be due to the xylanase compound isolated from Aspergillus niger in this study contains xylanase as well as other enzymes.…”
Section: The Mutant Xylanase Gene Expression In P Pastoris and Xylansupporting
confidence: 79%
“…The reason of the difference may be due to the different enzyme resources, xylanase purity or the modified xylanase gene (PUCHART et al, 2018). It was reported that xylanase gene from Bacillus licheniformis was expressed in E.coli, the enzyme was effective for sugarcane bagasse saccharification (AFTAB et al, 2018), in agreement with this study. In addition, the xylanase from Aspergillus niger could improve the yields of glucose and arabinose effectively (p<0.05), which may be due to the xylanase compound isolated from Aspergillus niger in this study contains xylanase as well as other enzymes.…”
Section: The Mutant Xylanase Gene Expression In P Pastoris and Xylansupporting
confidence: 79%
“…In another study, maximum saccharification potential was checked against sugarcane bagasse using the recombinant xylanase enzyme. 68 The saccharification efficiency obtained here be compared and discussed with saccharification efficiencies measured by other researchers are enlisted in Table 4.…”
Section: Discussionmentioning
confidence: 96%
“…But there is an infinite pool for men to play in. (Akhavan quoted in Aftab 2015) For Akhavan, these comparisons play a part in diminishing the value of her work to film culture. She also positions this in relative terms alongside the way that the work of her male peers has been seen and treated (she is certainly correct that hers is far from the only work to emerge from recent American independent cinema that bears obvious comparison with Allen's).…”
Section: Critical Reception Of Appropriate Behavior-the "Gay Annie Hall"mentioning
confidence: 99%